Expanding data is critical to assessing gendered impacts of household energy use. (14th October 2021) - Haddad, Zeenah; Williams, Kendra N; Lewis, Jessica J; Prats, Elena Villalobos; Adair-Rohani, Heather
Abstract : Zeenah Haddad and colleagues call for an expansion of data on household energy use routinely collected through national surveys to gauge the health effects by gender